Exploring E-Commerce Adoption in Small and Medium Enterprises (SMEs) using the Technology Acceptance Model - Laurina Trisnaning Putri; Adinda Putri Nur Aini; Nihayatu Aslamatis Solekah; Dyah Febriantina Istiqomah (International Journal of Business Economics (IJBE), 2023)
Purpose – Adoption of e-commerce by SMEs can contribute to regional economic growth, so this research aims to test and analyze the influence of the Actual Use of E-commerce with the Technology Acceptance Model (TAM) Approach on SMEs in Malang City.Methodology –  The approach used is quantitative with a survey of SMEs business actors who have used one of the e-commerce platforms, namely Shoppe, Tokopedia, Lazada, Blibli and Bukalapak, totalling 106 samples, with a quota sampling technique. SEM-PLS tests and measures the extent to which the conceptual model is built according to the empirical data collected.Findings – The results of this research prove that there is a significant positive contribution between perceived Usefulness towards Attitude Toward Using, no considerable contribution between Perceived Ease of Use towards Attitude Toward Using, there is a substantial contribution between Perceived Ease of Use towards Perceived Usefulness, there is a positive and significant contribution between Perceived Usefulness to Behavioral Intention to Use, there is a positive and meaningful contribution between Attitude Toward Using and Behavioral Intention to Use, there is a positive and significant contribution between Actual Behavioral Intention to Use and Actual Usage.Originality/Novelty :  The element of originality in the results of this research lies in specific findings that provide new insight into the factors that influence e-commerce adoption in the context of SMEs with the TAM approach, as well as the relationship between attitudes, intentions and real actions in using this technology.Implications – Help increase the adoption of e-commerce by SMEs, which in turn can contribute to the growth and development of SMEs' businesses as well as the economy as a whole.